Dragonfly (Odonata) Community Structure in Bandealit Resort, Meru Betiri National Park - Abdu Rohman; Wachju Subchan; Yusnia Faradilla; Puji Firmansyah (Jurnal Biodjati, 2025)
Bandealit Resort is a conservation area encompassing diverse habitats, providing a suitable environment for dragonflies to thrive as permanent inhabitants. The region plays a crucial role in supplying vital water for the life cycle of dragonflies. Human activities occurring in the upstream areas, such as agriculture, can potentially deteriorate water quality due to pollution. This work is highly significant due to the lack of recent monitoring data on dragonflies in the area and the pivotal role of dragonflies as bioindicators. This study aimed to analyze the composition and organization of the dragonfly population at Bandealit Resort (MBNP). A total of twelve dragonfly species were documented, among which were two species that are exclusive to Java. The Shannon-Wiener index study indicated a classification of modest diversity. The Terjun Block had the highest dominance index (D) of 0.27, whilst the Pringtali Block had the highest uniformity index (e^H/S) of 0.86. The species with the most excellent importance index (IVI) in different blocks are as follows: Euphaea variegata and Vestalis luctuosa in Pringtali Block, Nososticta insignis in Terjun Block, and Crocothemis servilia in East Muara Block. The canonical corresponding analysis (CCA) revealed that V. luctuosa, Heliocypha fenestrata, and Nososticta insignis exhibited a correlation with air humidity. In contrast, Copera marginipes, Pantala flavescens, C. servilia, and Diplacodes trivialis demonstrated a correlation with light intensity, wind speed, and air temperature. This research holds significance as it directly examines the relationship between dragonfly communities and abiotic parameters within the Bandealit Resort, Meru Betiri National Park (MBNP).